pH‐Dependent Assembly and Stability of Toll‐Like Receptor 3/dsRNA Signaling Complex: Insights from Constant pH Molecular Dynamics and Metadynamics Simulations - Penghui Li; Mingsong Shi; Yibo Wang; Qiong Liu; Xiubo Du; Xiaohui Wang (Advanced Science)
Abstract The pH‐dependent assembly of Toll‐like receptors (TLRs), which triggers a threshold‐like response, is a key principle in immune signaling. While crystallography has revealed the intricate structure of these assembly complexes, the mechanisms underlying their pH dependency remain unclear. Herein, constant pH simulations and metadynamics are employed to investigate the pH‐dependent assembly and stability of the TLR3/dsRNA signaling complex. The findings demonstrate that system pH regulates complex assembly and stability by modulating the protonation and charge states of histidines. Histidines in TLR3 act as pH‐dependent, positively charged binding sites that capture negatively charged dsRNA. Additionally, these histidines form a [H682⁺]—[E626⁻] dipole, facilitating the assembly of two TLR3 molecules into an antisymmetric dimer through dipole–dipole interactions. Surprisingly, TLR3 can shift the pKa values of key histidines from their model pKa of 6.5, increasing protonation likelihood and enhancing ligand binding. Notably, the aromatic residue Phe84, located within the dsRNA binding site [His39⁺–His60⁺–Phe84–His108⁺], alters the pKa of His60 through cation‐π interactions with its protonated state. This study offers new insights into the molecular mechanisms underlying pH‐dependent immune signaling via higher‐order assemblies and suggests potential applications for histidine in self‐assembling biomaterials.